Eosinophilic Esophagitis: Clinical Features, Endoscopic Findings and Response to Treatment - Robert Enns; Pooya Kazemi; Wiley Chung; Mitchell Lee (Canadian Journal of Gastroenterology)
Eosinophilic esophagitis (EE) is a motility disorder of the esophagus that typically presents with dysphagia. The objective of the present study was to explore patient characteristics, clinical and endoscopic features, and response to treatment of patients with EE. Patients were selected retrospectively based on a review of biopsy results from previous endoscopies performed between 2004 and 2008. A total of 54 patients (41 men and 13 women) with biopsy-proven EE were included in the study. Further information regarding the patients’ clinical and endoscopic features, and response to treatment were obtained through chart reviews and patient telephone interviews. The mean age of the patients at symptom onset was 30 years. All patients complained of dysphagia, 81% had a history of bolus obstruction, 43% had a history of asthma and 70% had a history of environmental allergies. Thirty-three per cent had a family history of asthma, while 52% had a family history of food or seasonal allergies. The most common endoscopic findings were rings and/or corrugations, which were found in 63% of patients. Swallowed fluticasone therapy resulted in symptom resolution in 74% of patients; however, 79% of these patients relapsed after discontinuing fluticasone therapy and required repeat treatments. Esophageal dilation was complication free and resulted in improvement in 80% of patients. However, 83% of those reporting improvement relapsed within one year. The clinical and endoscopic findings were similar to those found in the literature, with most patients requiring ongoing, repeated therapies. Further studies are needed to assess the safety and efficacy of treatment modalities ideally suited to patients with EE.